Exploiting Two‐Step Processed Mixed 2D/3D Perovskites for Bright Green Light Emitting Diodes. Issue 15 (10th May 2019) - Yan, Jielin; Croes, Guillaume; Fakharuddin, Azhar; Song, Wenya; Heremans, Paul; Chen, Hongzheng; Qiu, Weiming
Abstract: Mixed 2D/3D perovskite films with self‐assembled quantum wells have significantly improved the performance of perovskite light emitting diodes (PeLEDs). In this work, such films are fabricated through a two‐step interdiffusion method that is widely employed in processing of perovskite solar cells, however, remains rarely explored for PeLEDs. The effects of incorporating large‐cation ligand, i.e., butylammonium bromide (BABr) into formamidinium lead bromide (FAPbBr3 ) based perovskites, in terms of film composition, morphology, optoelectronic properties as well as device performance are thoroughly investigated in this method. By modulating BABr:PbBr2 ratio in the precursor solution, the optimal device shows a maximum external quantum efficiency (EQE) of 7.36% at 147.7 mA cm −2 and a brightness of 37 720 Cd m −2 at 5 V. The performance is remarkably higher than a reference device without BABr that shows a maximum EQE of 2.53% and a brightness of 6190 Cd m −2 at 5 V. The versatility of this method is further extended to another large‐cation ligand, 4‐fluoro‐benzylammonium bromide (F‐BZABr), which leads to maximum EQE of 8.55%. This work indicates two‐step processed mixed 2D/3D perovskites are promising for bright green PeLEDs. Abstract : Two‐step interdiffusion method is investigated for the preparation of mixed 2D/3D perovskite light emitting diodes. By incorporating large‐cation ligand to formamidinium lead bromide, devices show a maximum external quantum efficiency of 7.36% at 147.7 mA cm ‐2, and a narrow emission peak with full width at half maximum of 21 nm. This method is versatile for different types of organic ligands.